+0  
 
0
81
1
avatar

When the polynomial p(x) is divided by x - 1, the remainder is 3. When the polynomial p(x)$ is divided by x - 3, the remainder is 8. What is the remainder when the polynomial p(x) is divided by (x - 1)(x - 3)?

 Jun 16, 2021
 #1
avatar+524 
+2

According to remainder theorem 

  When a polynomial p(x) is divided by (x−a), the remainder is p(a).

When p(x) divided by x-1, remainder is 3

... p(1) = 3

When p(x) divided by x-3, remainder is 8

... p(3) = 8 

 

When p(x) is divided by (x-1)(x-3) let remainder be r(x) = ax + b

⇒ p(x) = (x-1)(x-3)q(x) + ax + b

p(1) = a + b = 3

p(3) = 3a + b = 8 

 

Subtracting p(1) from p(3)

2a = 5    ⇒ a = 5/2 

⇒ b = 1/2

 

Thus the remainder is   \(r(x) = {5\over 2}x+{1\over 2}\) 

 Jun 16, 2021

26 Online Users

avatar